Urgensitas Nilai Moral Kristiani dalam Pembentukan Karakter Anak Muda Katolik: Peran Pendidikan Moral di Smak Santo Peregrinus Laziosi Watumingan - Herlina Tiara A. Lendo; Yanto Sandy Tjang; Kristina Meni; Gabriel Babtis Tuta; Janti Sudono; Felisitas Yuswanto (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2026)
The study examines the urgency of Christian moral values in shaping the character of Catholic youth amid the dynamics of the digital era, marked by shifting values and identity crisis. The focus of the study is directed toward the role of Christian moral education at SMAK Santo Peregrinus Laziosi Watumingan as an integrative medium between faith and concrete life. This research employs a qualitative approach based on a literature review by critically and systematically analyzing relevant scholarly sources. This approach enables an in-depth conceptual exploration of the relationship between moral values, character formation, and the social context of Catholic youth. The findings reveal that Christian moral values, such as: honesty, truth, justice, courtesy, and respect for human dignity, play a fundamental role in forming a holistic person rooted in faith. These values are not merely taught as normative principles but are internalized through a learning process that emphasizes the interconnectedness between Gospel teachings and students’ lived realities. In this context, Christian moral education functions as a bridge that addresses the gap between faith and modern challenges, while fostering ethical awareness and social responsibility among learners. Therefore, this study affirms that Christian moral education holds strong relevance as a strategy for nurturing character and faith in the younger generation. The sustained internalization of values strengthens personal resilience in facing contemporary life and forms individuals capable of witnessing Gospel values daily. This study contributes conceptually to the development of contextual, reflective, and transformative character education within Catholic educational settings.